PENGEMBANGAN KOMPETENSI PROFESIONAL GURU PROGRAM KHUSUS PADA SDLB NEGERI BANDA ACEH - Lenayanti Br. Pulungan, Yusrizal, Niswanto (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2017)
ABSTRACT: Professional competence development of teachers is an activity undergone by teachers in the context of the practice of science, technology and skills to improve the quality of learning outcomes through teaching and learning process improvement. This study aimed to determine: the process of program drafting, development strategies as well as factors supporting and inhibiting the development of professional competence of teachers of special program in the State Elementary School for Students with Special Needs of Banda Aceh. This study used a qualitative approach with descriptive method. Data were collected through observation, interview, and documentation. Subjects of the study were principals, supervisors, vice principal, chairman of the school cluster, and teachers of special program. The results showed that: (1) program drafting was conducted by the principal, together with vice-principal and some teachers of special programs through a work meeting at the beginning of the new school year; (2) Strategies undertaken by the principal namely carrying out in-house training, sending teachers to take part in education and training program at the institution that provides training and education program, at local and national level, as well as providing opportunities for teachers to continue their education to a higher level; and (3) Supporting factors were: (a) teachers engaging in development program was in conformity with the needs and relevant to the existing competence; (b) There were a lot of training programs. While the inhibiting factors were: (a) The budget to carry out in-house training was limited; (b) The training program has not accommodated all types of existing specificities; (c) The development program was not sustainable; and (d) The level of mastery of technology of teachers of special programs was low.Keywords: development, professional competence and special program teachers ABSTRAK: Pengembangan komptensi profesional guru adalah kegiatan yang dilakukan oleh guru dalam rangka pengamalan ilmu pengetahuan, teknologi dan keterampilan untuk meningkatkan mutu hasil belajar melalui peningkatan proses belajar mengajar. Penelitian ini bertujuan untuk mengetahui: proses penyusunan program, strategi pengembangan serta faktor pendukung dan penghambat pengembangan kompetensi profesional guru program khusus pada SDLB Negeri Banda Aceh. Penelitian ini menggunakan pendekatan kualitatif, dengan metode deskriptif. Teknik pengumpulan data dilakukan dengan observasi, wawancara, dan dokumentasi. Subjek penelitian adalah kepala sekolah, pengawas, wakil kepala sekolah, ketua gugus, dan guru program khusus. Hasil penelitian menunjukkan bahwa (1) Penyusunan program dilakukan oleh kepala sekolah, bersama wakil kepala sekolah dan beberapa guru program khusus melalui rapat kerja pada awal tahun ajaran baru; (2) Strategi yang dilakukan oleh kepala sekolah yaitu mengadakan in house training, mengirim guru untuk mengikuti diklat ke lembaga penyelenggara pelatihan, di tingkat daerah, dan nasional, serta memberikan peluang bagi guru untuk melanjutkan pendidikan ke jenjang yang lebih tinggi; dan (3) Faktor pendukungnya adalah: (a) Guru yang mengikuti program pengembangan sudah sesuai dengan kebutuhan dan relevan dengan kompetensi yang ada; (b) Banyaknya program pelatihan yang diselenggarakan. Sedangkan faktor penghambatnya adalah: (a) Terbatasnya anggaran untuk melaksanakan in house training; (b) Program pelatihan belum mengakomodir semua jenis kekhususan yang ada; (c) Program pengembangan belum berkesinambungan; dan (d) Masih rendahnya tingkat penguasaan teknologi oleh guru program khusus.Kata kunci: pengembangan, kompetensi profesional, dan guru program khusus